COMPARATIVE ANALYSIS OF MACULAR THICKNESS IN AMBLYOPIC AND NON-AMBLYOPIC EYES IN CHILDREN (The Research of Medical Science Review, 2025)
Background: Amblyopia, commonly known as “lazy eye,” is a neurodevelopmental visual disorder characterized by reduced best-corrected visual acuity in one or both eyes, not attributable to any structural abnormality. It typically develops during early childhood due to abnormal visual experience caused by factors such as anisometropia, strabismus, or visual deprivation. Recent advances in imaging technologies, particularly spectral-domain optical coherence tomography (SD-OCT), have enabled detailed assessment of retinal structures, including macular thickness, which may be altered in amblyopic eyes. Understanding macular thickness differences between amblyopic and non-amblyopic eyes in pediatric patients could provide insights into the pathophysiology of amblyopia and potentially guide more targeted therapeutic interventions.Objective: To compare macular thickness between amblyopic and fellow eyes in children with unilateral amblyopia using spectral-domain optical coherence tomography (SD-OCT), and to explore the association between macular structural changes and amblyopia subtype.Material & Methods: This cross-sectional study was conducted at the Ophthalmology Department of Hayatabad Medical Complex, Peshawar, from August 2022 to December 2023. Seventy-five children aged 5–15 years with unilateral amblyopia were enrolled. Bilateral amblyopia and other ocular/systemic diseases were excluded. Comprehensive ophthalmologic examination including best-corrected visual acuity (BCVA), refractive error, and SD-OCT macular mapping was performed. Macular thickness in central, parafoveal, and average regions was compared between amblyopic and fellow eyes.Results: The mean age of participants was 9.2 ± 2.8 years, with a near-equal gender and laterality distribution. The mean central subfield thickness was significantly greater in amblyopic eyes (263.1 ± 18.4 µm) compared to non-amblyopic eyes (254.7 ± 17.6 µm; p < 0.001). Significant thickening was also observed in nasal (p = 0.005), temporal (p = 0.003), and average macular regions (p = 0.002), while superior and inferior parafoveal regions did not differ significantly. Subgroup analysis revealed more pronounced thickening in anisometropic amblyopia than strabismic amblyopia.Conclusion: Children with unilateral amblyopia exhibit increased macular thickness, particularly in the central and horizontal parafoveal regions. These anatomical changes may reflect developmental retinal immaturity and could influence visual prognosis. SD-OCT may serve as a valuable adjunct in the structural assessment of amblyopic eyes.